Macrophage Infiltration Initiates RIP3/MLKL-Dependent Necroptosis in Paclitaxel-Induced Neuropathic Pain - Dongyang Ma; Xiuli Wang; Xin Liu; Zhao Li; Jiaxin Liu; Jing Cao; Guiying Wang; Yuexian Guo; Shuang Zhao (Mediators of Inflammation)
Paclitaxel (PTX) is a commonly used antitumor drug. Approximately 80% of all patients receiving PTX chemotherapy develop chemotherapy-induced peripheral neuropathy (CIPN), limiting the use of PTX. Moreover, CIPN responds poorly to conventional analgesics. Experimental evidence suggests that the neuroinflammatory response plays an essential role in paclitaxel-induced peripheral neuropathy (PIPN). Previous studies have confirmed that dorsal root ganglion (DRG) neuron necroptosis and accompanying inflammation are linked with PIPN; however, the potential upstream regulatory mechanisms remain unclear. Preclinical studies have also established that macrophage infiltration in the DRG is associated with PIPN. TNF-α released by activated macrophages is the primary regulatory signal of necroptosis. In this study, we established a rat model of PIPN via quartic PTX administration (accumulated dose: 8 mg/kg, i.p.). The regulatory effect of macrophage infiltration on necroptosis in PIPN was observed using a macrophage scavenging agent (clodronate disodium). The results showed that PTX increased macrophage infiltration and the levels of TNF-α and IL-1β in the DRG. PTX also upregulated the levels of necroptosis-related proteins, including receptor-interacting protein kinase (RIP3) and mixed-lineage kinase domain-like protein (MLKL) in DRG neurons and promoted MLKL phosphorylation, resulting in neuronal necrosis and hyperalgesia. In contrast, clodronate disodium effectively removed macrophages, reduced the levels of RIP3, MLKL, and pMLKL, and decreased the number of necrotic cells in the DRG of PIPN rats, alleviating the behavioral pain abnormalities. These results suggest that PTX promotes macrophage infiltration, which results in the release of TNF-α and IL-1β in the DRG and the initiation of neuronal necroptosis via the RIP3/MLKL pathway, ultimately leading to neuropathic pain.